2014
DOI: 10.1089/cap.2014.0055
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Effect of Risperidone on Core Autistic Symptoms: Data from a Longitudinal Study

Abstract: Objective: The purpose of this study was to investigate the course of autistic symptoms, using a quantitative measure of core autistic traits, among risperidone-treated children who participated in a 10 year life course longitudinal study. Methods: Parents completed surveys of intervention history, as well as serial symptom severity measurements using the Social Responsiveness Scale (SRS), on their autism spectrum disorder (ASD)-affected children. Fifty participants (out of a total of 184 with full interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Second, due to the cohort‐sequential design, no individual was studied from early childhood to adulthood. Third, the affected subjects were receiving a variety of forms of therapy, and although their trajectories could have been influenced by the interventions, their SRS scores still remained stable (see also Marrus, Underwood‐Riordan, Randall, Zhang, & Constantino, ). Finally, this prospective longitudinal study lacked statistical power to fully define specific trajectories of subgroups of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Second, due to the cohort‐sequential design, no individual was studied from early childhood to adulthood. Third, the affected subjects were receiving a variety of forms of therapy, and although their trajectories could have been influenced by the interventions, their SRS scores still remained stable (see also Marrus, Underwood‐Riordan, Randall, Zhang, & Constantino, ). Finally, this prospective longitudinal study lacked statistical power to fully define specific trajectories of subgroups of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the approved dopamine receptor antagonist (risperidone) is of questionable benefit for cognition in ASD, as its antagonistic effects at dopamine receptors may interfere with precision-weighting of prediction errors, and thus updating of priors, in high-level regions of the cognitive hierarchy such as prefrontal cortex ( 91 ), which are critical for the development of abstract representations. Indeed, empirical studies demonstrate that core symptoms of ASD do not benefit from this medication ( 147 ). Perhaps not surprisingly, this purely symptomatic approach is rarely subjectively experienced as helpful by patients.…”
Section: Potential Benefits For Future Clinical Practicementioning
confidence: 99%
“…Duku et al [] investigated measurement invariance of the factor structure of the SRS and found that the factors of the SRS were stable across occasions. Marrus et al [] conducted a 10‐year longitudinal study of risperidone use in children with ASD and found that the SRS was sensitive to detecting change over time. Hasegawa et al [] demonstrated that an increase in parental empathy level was associated with an improvement of autism symptoms as measured by SRS.…”
Section: Introductionmentioning
confidence: 99%